Advances in Focused Retrieval 7th International Workshop of the Initiative for the Evaluation of XML Retrieval, INEX 2008, Dagstuhl Castle, Germany, December 15-18, 2009. Revised and Selected Papers - Geva, Shlomo; Kamps, Jaap; Trotman, Andrew (Information Systems and Applications, incl. Internet/Web, and HCI, 2009)
This book constitutes the thoroughly refereed proceedings of the 7th International Workshop of the Initiative for the Evaluation of XML Retrieval, INEX 2008, held at Dagstuhl Castle, Germany, in December 2008. The aim of the INEX 2008 workshop was to bring together researchers who participated in the INEX 2008 campaign. Over the year leading up to the event, participating organizations contributed to the building of a large-scale XML test collection by creating topics, performing retrieval runs, and providing relevance assessments. The workshop concluded the results of this large-scale effort, summarized and addressed the issues encountered, and devised a work plan for the future evaluation of XML retrieval systems. The 49 papers included in this volume report the final results of INEX 2008. They have been divided into sections according to the seven tracks of the workshop, investigating various aspects of XML retrieval, from book search to entity ranking, including interaction aspects.